PENGARUH PEMBERIAN MADU TERHADAP KADAR ALBUMIN PLASMA TIKUS PUTIH (Rattus norvegicus L.) JANTAN GALUR WISTAR YANG DI INDUKSI TUAK - MUHAMMAD EGGA ACHYAR RAHMAN; ROBITAH ASFUR; FANI ADE IRMA; EMNI PURWONINGSIH (JURNAL ILMIAH KOHESI, 2019)
Tuak is the result of fermentation of leads taken from aren (Arenga pinnata) containing 88% water, 11.8% carbohydrate, 0.23% protein, 0.02% fat, 0.03% minerals and 5% alcohol. Alcohol metabolism in liver cells leads to an increase in free radicals resulting in oxidative stress that damages tissues in the liver. Objective: This study aims to determine the effect of giving honey on white rats (Rattus norvegicus L.) male wistar-induced strain of tuak. Method: True experiment design "prettest-posttest with control group design". Results: Significant results of plasma albumin levels between control and treatment groups were p> 0.05. Conclusion: Provision of honey 1.35 mL /rat/ day for 15 days had an effect on the increase of plasma albumin level which previously decrease due tuak 2.5 mL /rat/ day for 15 days.